Film and television analysis : an introduction to methods, theories, and approaches - Benshoff, Harry M.; Murphy, Caryn (New York, NY : Routledge, 2024)
"This fully revised second edition textbook is especially designed to introduce undergraduate students to the most important qualitative methodologies used to study film and television. The methodologies covered in Film and Television Analysis include: ideological analysis, auteur theory, genre theory, semiotics and structuralism, psychoanalysis and apparatus theory, feminism, postmodernism, cultural studies (including reception and audience studies), and contemporary approaches to race, nation, gender, and sexuality. With each chapter focusing on a distinct methodology, students are introduced to the historical developments of each approach, along with its vocabulary, significant scholars, key concepts and case studies. Features of the second edition include: new and updated case studies to accompany each chapter over 130 color images throughout questions for discussion at the end of each chapter suggestions for further reading a glossary of key terms Written in a reader-friendly manner Film and Television Analysis is a vital textbook for students encountering these concepts for the first time"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Film criticism; Television criticism